2010
DOI: 10.1128/iai.00090-10
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Enteritidis tatB and tatC Mutants Are Impaired in Caco-2 Cell Invasion In Vitro and Show Reduced Systemic Spread in Chickens

Abstract: Salmonella enterica subsp. enterica serovar Enteritidis is a leading causative agent of gastroenteritis in humans. This pathogen also colonizes the intestinal tracts of poultry and can spread systemically in chickens. Transfer to humans usually occurs through undercooked or improperly handled poultry meat or eggs. The bacterial twin-arginine transport (Tat) pathway is responsible for the translocation of folded proteins across the cytoplasmic membrane. In order to study the role of the Tat system in the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 74 publications
0
41
0
Order By: Relevance
“…Notably, the TAT translocation system has also been demonstrated to play a role in the pathogenesis of model infections for many of these pathogens (8,16,19,33,38,71). TAT was initially not known to participate in the secretion of extracellular virulence factors (e.g., toxins) beyond the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the TAT translocation system has also been demonstrated to play a role in the pathogenesis of model infections for many of these pathogens (8,16,19,33,38,71). TAT was initially not known to participate in the secretion of extracellular virulence factors (e.g., toxins) beyond the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the genomes of some Mycobacterium tuberculosis strains can encode as many as four separate TAT-transported PlcH orthologs (37), while the Burkholderia pseudomallei genome encodes three (31), and Burkholderia mallei and Acinetobacter baumannii each encode two. Additionally, there is a growing number of other plant and animal bacterial pathogens where TAT has now been shown to be required for full virulence, including enterohemorrhagic E. coli O157:H7 (48), Salmonella enterica (38), Legionella pneumophila (15), Vibrio spp. (19,71), Yersinia pseudotuberculosis (33), Pseudomonas syringae (8), and Agrobacterium tumefaciens (16).…”
mentioning
confidence: 99%
“…Several studies indicate that a functional Tat system is required for many pathogenic bacteria, such as Pseudomonas syringae pv. tomato DC3000, S. enterica, Campylobacter jejuni, and Ralstonia solanacearum (5,(48)(49)(50)(51), to efficiently re- spond to diverse forms of physicochemical stresses. Indeed, our transcriptomic analysis of the Y. pseudotuberculosis ⌬tatC mutant revealed that a number of prominent stress-responsive genes were induced at both temperatures, and this number was higher during stationary-phase growth.…”
Section: Figmentioning
confidence: 99%
“…In S. Typhimurium, a mutation in msbB caused formation of elongated cells and a mutation in tatB or tatC (encoding twin arginine transport proteins required for transporting outer membrane components) caused long aggregate filaments to form (34,53). Although a mutation in somA (ybjX) suppressed many phenotypes associated with the msbB mutant, the phenotypes related to a single mutation in somA (ybjX) were not characterized in the previous study (53).…”
Section: Fig 10mentioning
confidence: 85%
“…The ZM100, ⌬virK, ⌬ybjX, ⌬virK ⌬ybjX, ⌬virK pWSKVirK, and ⌬ybjX pWSKYbjX strains were tested for their sensitivity to EDTA and deoxycholic acid (DOC) as previously described (34,35). Briefly, approximately 1 ϫ 10 8 CFU bacteria were added to warm 0.5% LB agar and the mixture was poured over 1.5% LB agar plates.…”
Section: Methodsmentioning
confidence: 99%